Hijas y padres (Journal of Parents and Teachers, 2014)
The author reflects on the relationship between fathers and daughters in the light of Martínez Roca's book Hijas y Padres. Thus, the content of the book is revealed, including some quotes from the book, which encourages reading and understanding it.
Keywords: library and education; library pym